Ultrafast Dynamics in Molecules, Nanostructures and Interfaces - Gurzadian, G G ... [et al.]. (Singapore ; World Scientific Pub. Co., 2014)
Primary events in natural systems or devices occur on extremely short time scales, and yet determine in many cases the final performance or output. For this reason research in ultrafast science is of primary importance and impact in both fundamental research as well as its applications. This book reviews the advances in the field, addressing timely and open questions such as the role of quantum coherence in biology, the role of excess energy in electron injection at photovoltaic interfaces or the dynamics in quantum confined structures (e.g. multi carrier generation). The approach is that of a monograph, with a broad tutorial introduction and an overview of the recent results. This volume includes selected lectures presented at Symposium on Ultrafast Dynamics of the 7th International Conference on Materials for Advanced Technologies.
1. Femtosecond real-time vibrational spectroscopy using ultrafast laser pulses / Takayoshi Kobayashi and Juan Du -- 2. Multidimensional optical spectroscopy using a pump-probe configuration: Some implementation details / Zhengyang Zhang and Howe-Siang Tan -- 3. High-sensitivity ultrafast transient absorption spectroscopy of organic photovoltaic devices / Alex J. Barker ... [et al.] -- 4. Transient absorption data analysis by soft-modelling / I. A. Howard ... [et al.] -- 5. Infrared ultrafast optical probes of photoexcitations in [symbol]-conjugated polymers/fullerene blends for photovoltaic applications / C.-X. Sheng, U. Huynh and Z. V. Vardeny -- 6. Ultrafast optical probing of carrier motion in conjugated polymers and blends for solar cells / Vidmantas Gulbinas ... [et al.] -- 7. Singlet fission in organic crystals / Lin Ma ... [et al.] -- 8. Mapping carrier diffusion in single silicon core-shell nanowires with ultrafast optical microscopy / Minah Seo ... [et al.] -- 9. Exciton dynamics and its regulation ability in photosynthesis / V. Balevicius, Jr., L. Valkunas and D. Abramavicius -- 10. Ultrafast intramolecular dynamics in novel star-shaped molecules for photovoltaic applications / Oleg V. Kozlov ... [et al.] -- 11. Nonlinear spectroscopy of interfaces and its application to organic electronics / Silvia G. Motti, Francisco C. B. Maia and Paulo B. Miranda -- 12. Photoinduced charge transfer dynamics at hybrid GaAs/P3HT interfaces / Jun Yin ... [et al.] -- 13. The first step in vision: Visualizing wavepacket motion through a conical intersection / Dario Polli ... [et al.] -- 14. Ultrafast investigation of energy and charge transfer in a prototypical photovoltaic blend / Guglielmo Lanzani, Ajay Ram Srimath Kandada and Daniele Fazzi -- 15. Vacancy-doped plasmonic copper chalcogenide nanocrystals with tunable optical properties / Ilka Kriegel ... [et al.].
Includes bibliographical references.
Electronic reproduction.
Keywords: Spectrum analysis -- Congresses; Laser spectroscopy -- Congresses; Electronic books